Clinical Profile of Children with Acute Febrile Encephalopathy in a Tertiary Health Care Center of Nepal - Sharma, Poonam; Sarmah, BK; Kayastha, Pawana; Shrestha, Asim; Tiwari, Damodar (Journal of Nepal Paediatric Society, 2016)
Background: Acute febrile encephalopathy is a common and severe neurological syndrome that is associated with significant morbidity and mortality in children. The etiologies differ according to geographical regions and appropriate and efficient protocols for investigations and management requires proper understanding of various potential etiologies. Methods: In this prospective observational study, 54 children of one month to 14 years presenting to the hospital with acute onset of fever with altered sensorium were clinically evaluated and investigated. Clinical examinations included temperature, pulse rate, heart rate, blood pressure, coma severity by GCS, respiratory pattern and detail systemic and CNS examination. Etiology of acute febrile encephalopathy was based on clinical history, examination and relevant laboratory investigations. Results: The incidence of acute febrile encephalopathy was 5.5% of the total hospital admissions. There were 35(64.8%) boys and 19(35.2%) girls. The maximum number of children 24(44.4%) were between one to five years of age. The most common presenting complains besides fever and altered sensorium were seizures and vomiting which was present in 59.3% and 46.3% of children respectively. Signs of meningeal irritation, hypertonia, brisk deep tendon reflexes and extensor plantar response was present in 50%, 24%, 29.6%, and 44.4% respectively. The diagnosis based on clinical findings and laboratory investigations were viral encephalitis 34(63%), bacterial meningitis 12(22.2%), cerebral malaria 4(7.4), enteric encephalopathy 3(5.6%) and hepatic encephalopathy 1(1.9%). Conclusion: Viral encephalitis and bacterial meningitis are the most common cause of acute febrile encephalopathy. Preventive strategies can be done to decrease the incidence. J Nepal Paediatr Soc 2015;35(3):224-230